القرار الإداري والسلطة التقديرية للإدارة في القانو ن الجزائري - نسرين عيدودي; إسمهان بوراس (My University, 2021)
Summary: The evolution of administrative work in the light of the diversity of the Department's activities and the diversity of its fields has been reflected positively in the legislature's engagement with the Department in the legal texts it promulgates to determine its competencies and control its powers. Having been treated in these texts as a machine for administrative work, She became freer to engage in her activities after being enabled by the legislator to appreciate her greater freedom and open her space for initiative and innovation s exercise of this authority in order to protect the principle of legality that the Department must exercise its discretion in Etah, The legislature therefore subjected its work and, in particular, the administrative decisions it issues at its discretion to judicial control as a guarantee of its non-arbitrariness and as protection of the rights and freedoms of individuals. ............... الملخص: انعكست التطوارت التي يشهدها العمل الإداري في ظل تعدد نشاطات الإدارة وتنوع مجالاتها ايجابا على تعامل المشرع مع الإدارة في النصوص القانونية التي يصدرها لتحديد اختصاصاتها وضبط سلطاتها، فبعد أن كانت تعامل في هذه النصوص على أنها آلة للعمل الإداري، أصبحت أكثر حرية عند ممارسة نشاطاتها بعد أن مكنها المشرع من سلطة التقدير التي تمنحها حرية أكبر وتفتح المجال أمامها للمبادرة والابتكار، لكنه بالمقابل وضع آليات للرقابة على ممارسة الإدارة لهذه السلطة حماية لمبدأ المشروعية الذي يتوجب على الإدارة أن تمارس سلطتها التقديرية في إطا ره، لذلك أخضع المشرع أعمالها وبشكل خاص القارارت الإدارية التي تصدرها وفقا لسلطتها التقديرية إلى الرقابة القضائية كضمانة لعدم تعسفها و كحماية لحقوق الأفارد وحرياتهم. ..................... Résumé : L’évolution du travail administratif à la lumière de la diversité des activités du Ministère et de ses domaines a été reflétée positivement dans l’engagement de l’Assemblée législative avec le Ministère dans les textes juridiques qu’elle promulgue pour déterminer ses compétences et contrôler ses pouvoirs. Ayant été traités dans ces textes comme une machine pour le travail administratif, Elle est devenue plus libre de s’engager dans ses activités après avoir été autorisée par le législateur à apprécier sa plus grande liberté et à ouvrir son espace d initiative et d innovation l exercice de ce pouvoir afin de protéger le principe de légalité que le Ministère doit exercer son discrétion dans Etah, Le législateur a donc soumis son travail et, en particulier, les décisions administratives qu’il émet à sa discrétion au contrôle judiciaire comme garantie de son caractère non arbitraire et comme protection des droits et libertés des personnes.